A trionychid turtle from the late aquitanian (Early miocene) of neochori (Grevena, western Macedonia, Greece) - Vlachos, Evangelos (2018)
The new specimen reported herein can be clearly attributed to a soft-shelled turtle of the cryptodiran clade Pan-Trionychidae. This clade has only been recently identified in the fossil record of Greece from the Pliocene of the Thessaloniki area (Vlachos et al., 2015) and the earliest late Miocene of Crete Island (Georgalis et al., 2016). All soft-shelled turtle fossils from Greece cannot be identifiable beyond Pan-Trionychidae (Georgalis & Joyce, 2017). The new find reported herein extends the presence of this clade to the early Miocene of Greece (late Aquitanian) and therefore currently represents the oldest Greek turtle. The previously oldest records of fossil turtles from Greece were Nostimochelone lampra Georgalis et al., 2013 from the late Burdigalian of the Zeugostasion Formation (see Georgalis et al., 2013 and references therein), and fragments of Testudines indet. from the middle-late Burdigalian of Karydia and Aliveri (Georgalis et al., 2017). Therefore, the soft-shelled fossil turtle reported herein extends the Greek fossil record of turtles to the Aquitanian. This is the first fossil turtle finding from the Mesohellenic Basin, providing further evidence of the presence of early Miocene Testudines in NW Greece. These preliminary results highlight the necessity of increasing fieldwork efforts in the Mesohellenic Basin, an area with extensive sediments of high fossil preservation potential, as additional finds from this region are expected to provide valuable information regarding the early history of turtles in Greece.